PERAN POKDARWIS DALAM SOSIALISASI PROTOKOL KESEHARTAN COVID-19 DI KAWASAN OBJEK WISATA RUMAH SINGGAH TUAN KADI PEKANBARU - Cindy Aprillisa; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Early in 2020 the world is tossed with the advent of the corona virus (covid-19). In the face of the covid-19 pandemic, all parties must rise and not continue to crash under the conditions, especially in the tourism sector. Pokdarwis is part of a society that plays a crucial role in recognizing awareness of the covid-19 health protocol in a tourist attraction. The assessment aims to know the role of pokdarwis in covid-19 socialization healyh protocol, recognizing the efforts pokdarwis performs in Covid-19 socialization of the acttractions Rumah Singgah Tuan Kadi.wich is an icon of Pekanbaru, has become one of the tourist acttraction areas that implement CHSE during the pandemic. The uses qualitative descriptive methods, the data collection techniques used in this study are observation, interviews, documentation, and literature studies. The informants in this study consisted of the head of Pokdarwis, the caretaker, and the coordinator of the tourism object area rumah Singgah Tuan Kadi Pekanbaru. in the stages of planning, implementation, and utilization stage have been done by Pokdarwis even if they have not been properly implemented. Pokdarwis efforts in the socialization of covid-19 health protocol by following BISA activities, and maintaining environmental sustainability by mutual assistance. Keywords: Role, Pokdarwis, Rumah Singgah Tuan Kadi.